ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN DISIPLIN POSITIF DI SEKOLAH DASAR - Amri, Khairul; Rahman, Anisa; Pane, Aina Ristanti; Yus, Anita; Setiawan, Deny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to analyze the leadership style of the school principal in implementing positive discipline at SD Negeri 101990 Bangun Purba. The research method used is descriptive method with a qualitative approach to examine the problems and obtain in-depth and meaningful information about the analysis of the school principal's leadership style in implementing disciplinary knowledge. This research was conducted at UPT SPF SDN 101990 Bangun Purba, with research subject is the school principal of UPT SPF SDN 101990 Bangun Purba as the subject. Based on the research conducted, the results show that the school principal at UPT SPF SDN 101990 Bangun Purba implements a democratic leadership style in implementing positive discipline at the school. In addition, the school principal also applies an approach that focuses on fostering and developing positive character in students through habituation activities, exemplary behavior, and rewarding students who have shown positive disciplinary behavior, as well as involving parents in efforts to foster students' character through parenting activities and intensive communication.